Counterion‐Assisted Shaping of Nanocluster Supracrystals. (5th November 2014) - Yao, Qiaofeng; Yu, Yue; Yuan, Xun; Yu, Yong; Zhao, Dan; Xie, Jianping; Lee, Jim Yang
Abstract: Ag44 ( p ‐MBA)30 4− ( p ‐MBA= para ‐mercaptobenzoic acid) nanocluster (NC) supracrystals (SCs) with customizable shapes can be obtained by simply altering the type and concentration of the counterions of the p ‐MBA ligands in the dimethylsulfoxide (DMSO)/water crystallization system. Changing the counterion of the p ‐MBA ligand from H + to Cs + eliminates the directional hydrogen bonds in the SCs, resulting in the packing of deprotonated Ag44 ( p ‐MBA)30 4− NCs into octahedral SCs, which is in stark contrast to the rhombohedral SCs that were formed by the packing of protonated Ag44 ( p ‐MBA)30 4− NCs in previous studies. Furthermore, the double layer of deprotonated Ag44 ( p ‐MBA)30 4− NCs is sensitive to charge screening induced by increasing the Cs + concentration, thereby providing a means to regulate the precipitation kinetics of the Ag44 ( p ‐MBA)30 4− NCs for SC shape engineering. Slow precipitation kinetics was found to favor over‐growth at the corners and edges of the octahedral SC nuclei, shaping the SCs into concave octahedra. Abstract : Nanocluster‐Suprakristalle : Durch den Austausch der H + ‐Gegenionen durch Cs + ‐Ionen werden oktaedrische Ag44 ‐Nanocluster‐Suprakristalle statt der kürzlich beschriebenen Rhomboeder erhalten. Die oktaedrischen Suprakristalle können durch das Anpassen der Cs + ‐Konzentration entweder mit konkaven oder mit konvexen Seiten gebildet werden.